Regressing forward: Agriculture mechanization subsidy modalities in Bihar and Odisha - Saini, Smriti; Kishore, Avinash; Alvi, Muzna; International Maize and Wheat Improvement Center; International Rice Research Institute (Cereal Systems Initiative for South Asia, 2020)
Farm mechanization is indispensable for enhancing agricultural productivity across the country. Over the years, the Indian government has instituted several schemes and programs to promote agricultural mechanization in the country. Until recently, state and central government schemes took the form of price subsidies, especially targeting critical farm equipment. More recently, the government has shifted to direct benefit transfers (DBT) for all agricultural inputs, including farm implements. While the central government instituted the broader schemes and programs, the specifics concerning subsidy disbursement have been left to state governments, with flexibility on which implements to promote and how much and when to disburse subsidy payments. These broad guidelines have been enshrined in several programs, chief among which is the National Mission on Agriculture Extension and Technology (NMAET).